Spondylosis Deformans: A Clinical Case in a Beagle - I Putu Gede Yudhi Arjentinia; I Gede Soma; Elisabeth Karina (Journal of Veterinary and Animal Sciences, 2023)
Spondylosis is a degenerative disorder that causes abnormalities in the normal structure and function of the spine. A Beagle dog named Poby with female sex, tricolor color, 7 years old, weighing 18 kg came with complaints of sudden paralysis from one month ago before examination, the dog had difficulty passing stool so that the stomach was enlarged. Both eyes were droopy and sometimes red. Digestion examination an enlarged abdomen and when percussed there was a muffled sound and palpation urinary examination showed distension of the urinary vesica. The musculoskeletal examination showed that the case dog had muscle atrophy in both front legs and hind legs, the movement of both front legs and both hind legs was stiff, the muscle tension was weak, there was an uncomfortable reflex when palpated in the lumbar region, along with the neurological examination the dog had tetraplegia, there were no patellar reflexes, biceps, triceps, flexors, extensors on the right front and hind legs. Eye examination showed the nictitating membrane of the eye was up and the dog's eye was red. X-ray examination showed osteophytes in lumbar Os II-V, distension of the urinary vesica and accumulation of feces in the colon. The results of the CBC examination were that the case dog had mild lymphocytopenia, mild hypochromia, and hyperglycemia. The case dog was diagnosed with spondylosis. Treatment was carried out by administering Prednisone and acupuncture therapy. After the 50st day of treatment, the dog's condition improved.